2018
DOI: 10.1002/jat.3666
|View full text |Cite
|
Sign up to set email alerts
|

Protective potential of glutathione peroxidase‐1 gene against cocaine‐induced acute hepatotoxic consequences in mice

Abstract: Since the cocaine-induced oxidative stress has been established to lead to hepatotoxicity, we examined the role of the glutathione peroxidase (GPx)-1 gene in cocaine-induced hepatotoxicity. Cocaine treatment significantly increased superoxide dismutase activity in as little as 1 hour, with a maximum level at 6 hours in wild-type mice, while significantly decreasing GPx activity and subsequently inducing oxidative damage (i.e., reactive oxygen species, lipid peroxidation and protein carbonylation). These change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…There were significant increases in SOD activity, ROS, protein carbonylation and lipid peroxidation, cleaved caspase-3 expression and intramitochondrial calcium, accompanied by a significant decrease in GPx. Examples of histological changes include hemorrhage, congestion, periventricular necrosis and hydropic degeneration [124]. Notably, enhanced expression of GPx protected the animals from having such severe outcomes, as did the depletion of p53 [125].…”
Section: Livermentioning
confidence: 98%
“…There were significant increases in SOD activity, ROS, protein carbonylation and lipid peroxidation, cleaved caspase-3 expression and intramitochondrial calcium, accompanied by a significant decrease in GPx. Examples of histological changes include hemorrhage, congestion, periventricular necrosis and hydropic degeneration [124]. Notably, enhanced expression of GPx protected the animals from having such severe outcomes, as did the depletion of p53 [125].…”
Section: Livermentioning
confidence: 98%
“…Although the detailed cell death signaling mechanisms are unknown, one recent report showed that cocaine toxicity was attenuated in p53-knockout (p53-KO) mice, suggesting the involvement of the p53-mediated apoptosis pathway [ 295 ]. A recent study showed that cocaine caused mitochondrial dysfunction and acute liver injury in WT mice, and hepatotoxicity was prominently observed in Gpx-1 -KO mice but protected in Gpx1-overexpressing transgenic mice [ 66 ]. Based on the importance of PTMs in mitochondrial dysfunction and hepatocyte cell death in DILI, ALD, and MASLD models, the contributing roles of various PTMs in cocaine-mediated mitochondrial dysfunction and hepatotoxicity are expected, although this needs to be verified by future research.…”
Section: The Causal Roles Of Oxidative Stress Ptms Mitochondrial Dysf...mentioning
confidence: 99%
“…The proteins involved in promoting various PTMs exist in several subcellular organelles, including the cytoplasm [ 39 ], ER [ 40 , 41 ], mitochondria [ 42 ], and nucleus [ 43 ]; PTMs may also be observed in the proteomes of the liver [ 37 , 44 47 ], gut [ 7 ], and other peripheral tissues [ 29 ]. PTMs found in liver diseases include protein acetylation [ 37 , 42 , 48 ], nitration [ 10 , 26 , 37 , 49 53 ], S -nitrosylation [ 49 , 54 , 55 ], oxidation [ 37 ], phosphorylation [ 26 , 56 , 57 ], succinylation [ 58 ], ADP-ribosylation [ 44 ], ubiquitination [ 37 , 59 ], SUMOylation [ 60 65 ], carbonylation [ 66 68 ], S -palmitoylation [ 45 47 , 69 ], glycosylation [ 7 , 37 , 70 , 71 ], protein adducts of aldehyde (i.e., acetaldehydes) [ 9 , 72 ], lipid peroxidation products (LPOs), and advanced glycation end products (AGEs) [ 6 , 66 , 74 79 ]. Several studies detail that specific PTMs correlate with exposures to excessive alcohol [ 80 , 81 ], CCl 4 [ 7 , 56 ], acetaminophen (APAP) [ 53 , 82 ], 3,4-methylenedioxymethamphetamine (MDMA, Ecstasy) [ 39 ], or fructose [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations